Effects of fucoidan and synbiotics supplementation during bismuth quadruple therapy of Helicobacter pylori infection on gut microbial homeostasis: an open-label, randomized clinical trial - Wang, Huifen; Wei, Wei; Liu, Fang; Wang, Miao; Zhang, Yanli; Du, Shiyu (Frontiers in Nutrition, 2024)
The eradication regimen for Helicobacter pylori (H. pylori) infection can induce gut dysbiosis. In this open-label, prospective, and randomized clinical trial, we aimed to assess the effects of fucoidan supplementation on the eradication rate and gut microbial homeostasis in the context of quadruple therapy, as well as to investigate the combined effects of fucoidan and synbiotics supplementations.Methods: Eighty patients with H. pylori infection were enrolled and randomly assigned to one of four treatment groups: the QT (a 2-week quadruple therapy alone), QF (quadruple therapy plus a 6week fucoidan supplementation), QS (quadruple therapy plus a 6-week synbiotics supplementation), and QFS (quadruple therapy with a 6-week fucoidan and synbiotics supplementation), with 20 patients in each group. The QT regimen included rabeprazole, minocycline, amoxicillin, and bismuth potassium citrate. The synbiotics supplementation contained three strains of Bifidobacterium, three strains of Lactobacillus, along with three types of dietary fiber. All of the patients underwent 13 Curea breath test ( 13 C-UBT) at baseline and at the end of the 6th week after the initiation of the interventions. Fresh fecal samples were collected at baseline and at the end of the 6th week for gut microbiota analysis via 16S rRNA gene sequencing.The eradication rates among the four groups showed no significant difference. In the QT group, a significant reduction in α-diversity of gut microbiota diversity and a substantial shift in microbial composition were observed, particularly an increase in Escherichia-Shigella and a decrease in the abundance of genera from the Lachnospiraceae and Ruminococcaceae families. The Simpson index was significantly higher in the QF group than in the QT group. Neither the QS nor QFS groups exhibited significant changes in α-diversity or β-diversity. The QFS group was the only one that did not show a significant increase in the relative abundance of Escherichia-Shigella, and the relative abundance of Klebsiella significantly decreased in this group.The current study provided supporting evidence for the positive role of fucoidan and synbiotics supplementation in the gut microbiota. The combined use of fucoidan and synbioticss might be a promising adjuvant regimen to mitigate gut dysbiosis during H.pylori eradication therapy.